A Potential Antitumor Effect of Dendritic Cells Fused with Cancer Stem Cells in Hepatocellular Carcinoma - Ye-Bin Pang; Jian He; Bi-Yu Cui; Sheng Xu; Xi-Lei Li; Man-Ya Wu; Rong Liang; Yan Feng; Xing Guo; Xue-Hui Zhang; Xiao-Ling Luo (Stem Cells International)
HCC stem cells were reported as posttreatment residual tumor cells that play a pivotal role in tumor relapse. Fusing dendritic cells (DCs) with tumor cells represents an ideal approach to effectively activate the antitumor immunity in vivo. DC/HCC stem cell vaccine provides a potential strategy to generate polyclonal immune response to multiple tumor stem cell antigens including those yet to be unidentified. To assess the potential capacity of DC/HCC stem cell vaccines against HCC, CD90+HepG2 cells were sorted from the HCC cell line HepG2. DC and CD90+HepG2 and DC and HepG2 fused cells were induced by polyethylene glycol (PEG). The influence of fusion cells on proliferation and immunological function transformation of lymphocytes was assessed by FCM and ELISA assay, respectively. The cytotoxicity assay of specific fusion cell-induced CTLs against HepG2 was conducted by CytoTox 96 Non-Radioactive Cytotoxicity Assay kit in vitro. At last, the prevention of HCC formation in vivo was described in a mouse model. The results of FCM analysis showed that the proportion of CD90+HepG2 cells in the spheral CD90+HepG2 enriched by suspension sphere culture was ranging from 98.7% to 99.5%, and 57.1% CD90+HepG2/DC fused cells were successfully constructed. The fusion cells expressed a higher level of costimulatory molecules CD80, CD83, CD86, and MHC-I and MHC-II molecules HLA-ABC and HLA-DR than did immature DCs (P<0.05). And the functional analysis of fusion cell-induced CTLs also illustrated that CD90+HepG2/DC fusion cells showed a greater capacity to activate proliferation of lymphocytes in vitro (P<0.05). The CD90+HepG2/DC-activated CTLs had a specific killing ability against CD90+HepG2 cells in vivo. These results suggested that CD90+HepG2/DC fusion cells could efficiently stimulate T lymphocytes to generate specific CTLs targeting CD90+HepG2 cells. It might be a promising strategy of immunotherapy for HCC.